APPLICATION OF NEW TECHNOLOGIES IN THE EDUCATIONAL PROCESS: APPLICATION OF NEW TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Koldashev, Sirojjon (Физическое воспитание, спорт и здоровье, 2022)
Theoretical views on the process of acquiring new technologies, knowledge, skills and abilities in the educational process